Hip Sublime Beat Writers and the Classical Tradition - Murnaghan, Sheila; Rosen, Ralph (Classical Memories/Modern Identities Paul Allen Miller and Richard H. Armstrong, Series Editors, 2017)
In their continual attempt to transcend what they perceived as the superficiality, commercialism, and precariousness of life in post-World War II America, the Beat writers turned to the classical authors who provided, on the one hand, a discourse of sublimity to help them articulate their desire for a purity of experience, and, on the other, a venerable literary heritage.This volume examines for the first time the intersections between the Beat writers and the Greco-Roman literary tradition. Many of the "Beats" were university-trained and highly conscious of their literary forebears, frequently incorporating their knowledge of Classical literature into their own avant-garde, experimental practice. The interactions between writers who fashioned themselves as new and iconoclastic, and a venerable literary tradition often seen as conservative and culturally hegemonic, produced fascinating tensions and paradoxes, which are explored here by a diverse group of contributors.